Phenolic Compounds and Antioxidant Capacity of Sea Cucumber (Cucumaria frondosa) Processing Discards as Affected by High-Pressure Processing (HPP) - Abul Hossain; JuDong Yeo; Deepika Dave; Fereidoon Shahidi (Antioxidants, 2022)
Sea cucumber processing discards, which include mainly internal organs, represent up to 50% of the sea cucumber biomass, and are a rich source of bioactive compounds, including phenolics. This work aimed to extract free, esterified, and insoluble-bound phenolics from the internal organs of the Atlantic sea cucumber (C. frondosa) using high-pressure processing (HPP) pre-treatment. The sea cucumber internal organs were subjected to HPP (6000 bar for 10 min), followed by the extraction and characterization of phenolics. Samples were evaluated for their total contents of phenolics and flavonoids, as well as several in vitro methods of antioxidant activities, namely, free radical scavenging and metal chelation activities. Moreover, anti-tyrosinase and antiglycation properties, as well as inhibitory activities against LDL cholesterol oxidation and DNA damage, were examined. The results demonstrated that HPP pre-treatment had a significant effect on the extraction of phenolics, antioxidant properties, and other bioactivities. The phenolics in sea cucumber internal organs existed mainly in the free form, followed by the insoluble-bound and esterified fractions. Additionally, UHPLC-QTOF-MS/MS analysis identified and quantified 23 phenolic compounds from HPP-treated samples, mostly phenolic acids and flavonoids. Hence, this investigation provides fundamental information that helps to design the full utilization of the Atlantic sea cucumber species and the production of a multitude of value-added products.